Contralateral Ovarian Metastasis of Clear-Cell Renal Carcinoma: A Rare Case Report and Review of the Literature - Fatih Uruc; Serkan Akan; Aytaç Sahin; Caglar Yildirim; Ahmet Urkmez (Case Reports in Surgery)
Renal cell carcinoma (RCC) constitutes 2-3% of all types of cancers. RCCs metastasize into lungs (50–60%), lymph nodes (36%), bones (30–40%), liver (30–40%), and brain (5%) in respective percentages. RCC rarely metastasizes into ovary. Only 25 cases of ovarian tumor, which metastasized into kidneys, have been presented. In the literature, a kidney-ovary axis has been defined, and its interrelationship begins with embryological life. With this case report, we aimed both to present a very rarely seen metastasis of RCC into contralateral ovary and also to review the literature.